2022
DOI: 10.3390/antib11030054
|View full text |Cite
|
Sign up to set email alerts
|

Anticalin N- or C-Terminal on a Monoclonal Antibody Affects Both Production and In Vitro Functionality

Abstract: Bispecific antibodies (BsAbs) represent an important advance in innovative therapeutic strategies. Among the countless formats of BsAbs, fusion with molecules such as anticalins linked to a monoclonal antibody (mAb), represents an easy and low-cost way to obtain innovative molecules. We fused an anticalin against human fibronectin to a molecule biosimilar to trastuzumab (H0) or rituximab (R0), in four different positions, two on the N terminal region of heavy or light chains and two on the C terminal region. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…We also did not observe TLR2 binding with the Bic05 long linker on HEK-TLR2 cells as compared with the short linker format (i.e., Bic05) (data not shown). G4S is usually considered a rigid link, but other studies in the lab showed that this type of linker could be flexible with real degrees of freedom ( 38 ). The long linker providing larger degrees of freedom to scFVs might be deleterious.…”
Section: Discussionmentioning
confidence: 99%
“…We also did not observe TLR2 binding with the Bic05 long linker on HEK-TLR2 cells as compared with the short linker format (i.e., Bic05) (data not shown). G4S is usually considered a rigid link, but other studies in the lab showed that this type of linker could be flexible with real degrees of freedom ( 38 ). The long linker providing larger degrees of freedom to scFVs might be deleterious.…”
Section: Discussionmentioning
confidence: 99%